2021
DOI: 10.3389/fcvm.2021.693731
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Improves the Short-Term Medical Care of Acute ST-Segment Elevation Myocardial Infarction After Primary Percutaneous Coronary Intervention

Abstract: Objectives: Telemedicine appears to be a promising tool for healthcare professionals to deliver remote care to patients with cardiovascular diseases especially during the COVID-19 pandemic. We aimed in this study to evaluate the value of telemedicine added to the short-term medical care of acute ST-segment elevation myocardial infarction (STEMI) after primary percutaneous coronary intervention (PCI).Methods: Two hundred acute STEMI patients after primary PCI were randomly divided into two groups. One hundred p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…These studies were conducted in North America ( n = 5) ( 22 26 ), Europe ( n = 10) ( 14 , 27 35 ), Asia ( n = 9) ( 19 , 36 43 ), Africa ( n = 1) ( 44 ), Australia and New Zealand ( n = 6) ( 45 50 ), South America ( n = 1) ( 13 ). We included participants who were diagnosed with MI ( 24 , 29 , 32 , 34 , 35 , 37 , 44 , 47 ), ACS ( 14 , 22 , 31 , 33 , 49 ), CHD ( 13 , 19 , 23 , 27 , 28 , 30 , 40 , 41 , 45 , 46 , 48 , 50 ), Ischemic stroke ( 13 , 30 ) and PAD ( 13 , 19 , 30 ) or received coronary revascularization ( 13 , 19 , 23 , 25 , 26 , 28 , 29 , 33 , 36 , 38 , 39 , 42 , 43 , 45 , 48 , 49 ) in our review. The participants’ mean age varies from 55.8 to 70.36 and 20.04% of them are female.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were conducted in North America ( n = 5) ( 22 26 ), Europe ( n = 10) ( 14 , 27 35 ), Asia ( n = 9) ( 19 , 36 43 ), Africa ( n = 1) ( 44 ), Australia and New Zealand ( n = 6) ( 45 50 ), South America ( n = 1) ( 13 ). We included participants who were diagnosed with MI ( 24 , 29 , 32 , 34 , 35 , 37 , 44 , 47 ), ACS ( 14 , 22 , 31 , 33 , 49 ), CHD ( 13 , 19 , 23 , 27 , 28 , 30 , 40 , 41 , 45 , 46 , 48 , 50 ), Ischemic stroke ( 13 , 30 ) and PAD ( 13 , 19 , 30 ) or received coronary revascularization ( 13 , 19 , 23 , 25 , 26 , 28 , 29 , 33 , 36 , 38 , 39 , 42 , 43 , 45 , 48 , 49 ) in our review. The participants’ mean age varies from 55.8 to 70.36 and 20.04% of them are female.…”
Section: Resultsmentioning
confidence: 99%
“…These components are key building blocks of a basic telehealth program and without their proper access, one cannot operate efficient and equitable telehealth services that cover the entire population of the country. A study in Egypt assessed the challenges of telehealth services, where 37 patients reported a lack of smartphones and 29 patients reported a lack of poor internet connectivity out of 200 patients [ 47 ]. Another study in Mexico found the most frequent issues to be interruptions (14.7%), problems with Internet connectivity (12.8%), and poor-quality video/audio (12.2%) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 RCTs with a modified Jadad score lower than 5 points, indicating poor quality ( Table 1 ). 6 , 12 The RoB2 tool demonstrated that 9 of 11 RCTs had some concerns, due to bias arising from the randomization process and the lack of blinding in those studies 1 , 5 - 7 , 9 , 10 , 12 , 14 , 15 ( Figure 2A ). The ROBINS-I tool showed that the study conducted by Marvel et al might have had a serious risk of bias, due to the occurrence of a confounding risk ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it enabled patients to take their medications and exercise regularly by sending remainder messages or informing the risk factors of heart attack in a systematic way 3 , 5 - 9 , 11 , 14 Video conferences were arranged with patients to determine plans and goals, check for symptoms of patients and drug adherence, and control the need of laboratory analysis in 3 of 13 studies. 10 , 11 , 15 Lastly, a mobile application was used in 4 of 13 studies and it gathered the data of the physical activity, blood pressure measurements, heart rate, electrocardiograms, body weight, self-rating scale of symptom for HCPs, and helped patients to manage their medications, gave information about the risk factors of ischemic heart diseases via a telephone or a smartwatch. 5 , 12 - 15 The recent studies were designed with more updated technologies, such as digital recorders, video conferences, mobile applications, and smartwatches instead of mobile text message or telephone calls.…”
Section: Discussionmentioning
confidence: 99%